ONLINE DISINHIBITION AND ANONYMITY IN ADOLESCENT TIKTOK DISCOURSE: IMPLICATIONS FOR CYBERBULLYING AND DIGITAL EDUCATION - Juliati, Kurnia; Nugroho, Sigit; Qorifah, Nasha Nuryati (ppjbsip, 2025)
This study explores the relationship between online disinhibition, perceived anonymity, and cyberbullying behavior among adolescent TikTok users through a psychological and educational discourse lens. As social media becomes increasingly integrated into youth identity formation, understanding how digital environments shape speech patterns and behavioral norms is crucial. The research surveyed 297 adolescents aged 13–20 using validated psychometric scales and analyzed results via multiple linear regression. Findings reveal that both online disinhibition and anonymity significantly predict cyberbullying behavior, with anonymity (β = 0.670) exerting a stronger influence than disinhibition (β = 0.173). These results suggest that adolescents are more likely to engage in aggressive digital discourse when they feel untraceable or emotionally disconnected from their targets. TikTok’s unique algorithmic environment, pseudonym options, and asynchronous comment features reinforce this behavioral pattern. From an educational discourse perspective, these findings demonstrate that cyberbullying is not merely a behavioral outcome, but also a discursive shift where ethical communication norms erode under perceived invisibility. This study highlights the need for digital literacy programs that go beyond rule-based safety education to address the discursive realities of online interaction, emphasizing moral reasoning, identity accountability, and empathetic speech. Schools and educators should integrate reflective tasks that analyze online comment culture, encourage discourse analysis of aggressive digital speech, and cultivate a sense of online moral agency. Future research should investigate how specific language forms (e.g., sarcasm, mockery, tag-chaining) evolve in anonymous platforms and affect adolescent behavior. This research contributes to both cyberpsychology and education by providing a nuanced understanding of how digital speech patterns fueled by anonymity and disinhibition construct and normalize cyber aggression among youth